Analisis Perilaku Bullying Terhadap Motivasi Belajar Siswa Sekolah Dasar - Rachmatia Tauhid (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
This research aims to explore the forms and impacts of bullying behavior on students. This research uses a qualitative method with a case study approach. Data sources were taken through in-depth interviews with twenty informants consisting of elementary school students, teachers, school principals and parents. All interview data was then analyzed thematically using NVivo 10 qualitative analysis software. Overall the research results found nine important themes related to the form and impact of bullying behavior on students. The nine themes are divided into three themes related to forms of bullying behavior, namely i) physical, ii) verbal, iii) psychological. Furthermore, there are six themes related to the impacts, namely; i) loss of self-confidence, ii) intimidation, iii) low self-esteem, iv) feelings of insecurity and comfort, v) fear of socializing with the environment and vi) difficulty concentrating on studying. Bullying behavior has no place in the world of education, but in fact this problem often arises repeatedly without knowing the time and place. In fact, according to the author, all parties, not only schools, parents and the community, have an active role in preventing it from happening again, because based on this research, bullying behavior has a negative impact on students both physically and psychologically.